Um retorno ao inconsciente freudiano - Zaidan, Eduardo (2019)
This work explores the Freudian concept of the unconscious. The Lacanian axiom that “the unconscious is structured as a language” and Melanie Klein’s concept of sexual drive are investigated to discern their compatibility with Freudian thought. The Freudian theory of representation is presented and discussed in support of this debate. Freud’s references are presented in the form of historical research. Inspired by structuralism, Lacan’s concept of the primacy of the signifier and his theories on the subject’s constitution and psychopathology are confronted and criticized. An investigation of whether or not Freud had a developmentalist’s conception of the psychic apparatus is pursued. The concept of an a priori bond between sexual drive and an object is discussed and refuted so that the body’s role in psychic sexuality can be questioned and worked out using Freud’s notion of “attachment”. Freud’s texts are presented in chronological order. The advantages and disadvantages of different interpretations are evaluated in order to disengage from dogmatic adherence to Freudian theories